Codex Schøyen 2650 : a Middle Egyptian Coptic witness to the early Greek text of Matthew's Gospel : a study in translation theory, indigenous Coptic, and New Testament textual criticism - Leonard, James M., 1962- (New Testament Tools, Studies and Documents, 2014)
In 2001, the exciting but enigmatic 4th century Coptic Matthew text, Codex Schøyen, was introduced as an alternative, non-canonical Matthew. In this book, James M. Leonard refutes these sensational claims through fresh methodological approaches and easily accessible analysis. Leonard reveals that the underlying Greek text is one of great quality, and that Codex Schøyen can contribute to the identification of the earliest attainable text-but only with due concern for translational interference. Leonard shows how Codex Schøyen's close alliance with Codices Vaticanus and Sinaiticus allows triangulation of the three to help identify an earlier text form which they mutually reflect, and how this impacts a dozen variant passages in Matthew.